Morphological alterations within the peripheral fixation of the iris dilator muscle in eyes with pigmentary glaucoma - Flügel-Koch, Cassandra; Tektas, Ozan Yüksel; Kaufman, Paul L.; Paulsen, Friedrich; Lütjen-Drecoll, Elke (Investigative Ophthalmology & Visual Science, 2014)
To analyze the peripheral fixation of the iris dilator muscle in normal eyes and in eyes with pigmentary glaucoma (PG).Using 63 control eyes (age 18 months-99 years), the peripheral iris dilator was investigated by light microscopy, immunohistochemistry, and electron microscopy. Development was studied using 18 differently aged fetal eyes stained immunohistochemically against ?-smooth muscle (SM) actin. The peripheral iris dilator muscle in PG was analyzed using semithin and ultrathin sections of six glutaraldehyde-fixed eyes from three donors aged 38, 62, and 74 years.In normal eyes, the peripheral end of the iris dilator muscle is arranged in a sphincter-like manner. Arcade-shaped tendinous connections associated with myofibroblasts (iridial strands) anchor the iris dilator within the elastic-fibromuscular ciliary meshwork that also serves as fixation area for the elastic tendons of the inner ciliary muscle portions. The iridial strands are innervated and can adapt their length during accommodation. The PG eyes show incomplete circular bundles and iridial strands that are mainly anchored to the iris stroma and the flexible uveal parts of the trabecular meshwork.The normal anchorage of the peripheral iris dilator and its presumably neuronally regulated length adaptation stabilize the peripheral iris during accommodation. Insufficient fixation in PG could promote posterior bowing of the iris with rubbing against the zonular fibers and pigment liberation from the iris pigmented epithelium.
EVALuna2:4417